Processamento distribuído da consulta espaço textual top-k - Novaes, Tiago Fernandes de Athayde (2017)
With the popularization of databases containing objects with spatial and textual information (spatio-textual object), the interest in new queries and techniques for retrieving these objects have increased. In this scenario, the main query is the the top-k spatio-textual query. This query retrieves the k best spatio-textual objects considering the distance of the object to the query location and the textual similarity between the query keywords and the textual information of the objects. However, most the studies related to top-k spatio-textual query are performed in centralized environments, not addressing real world problems such as scalability. In this paper, we study different strategies for partitioning the data and processing the top-k spatio-textual query in a distributed environment. We evaluate each strategy in a real distributed environment, employing real datasets.